Thermoplastic resin composition

By adding thermoplastic polyurethane to the methacrylic resin composition, the composition and structure of the resin are optimized, and the toughness and transparency of existing resins when used outdoors are solved, and the thermoplasticity with high transparency, toughness and damage resistance are achieved. Resin composition.

CN115023465BActive Publication Date: 2025-02-14ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202180011430.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-10
Filing Date
2021-02-04
Publication Date
2025-02-14
Estimated Expiration
2041-02-04

AI Technical Summary

Technical Problem

The conventional methacrylic resin composition has problems such as low toughness and surface damage when used outdoors, and it is easy to cause stress whitening when improving toughness, and there is still room for improvement in transparency and damage resistance.

Method used

A composition is used in which 50 to 99 mass% of the methacrylic resin (A) and 1 to 50 mass% of the thermoplastic polyurethane (B), wherein the methacrylic resin (A) is 80.0 to 99.9 mass% of the methacrylic acid The ester monomer unit, 0.1 to 20.0 mass % of vinyl monomer unit, and 0 to 4.0 mass % of maleic acid and/or maleic anhydride monomer unit, the thermoplastic polyurethane (B) has a polyester polyol and has a The structural unit of the isocyanate of the alicyclic ring.

Benefits of technology

It is achieved to reduce haze while maintaining high transmittance, improve transparency, toughness and damage resistance, and form an excellent thermoplastic resin composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003767660370000181
    Figure GDA0003767660370000181
  • Figure GDA0003767660370000191
    Figure GDA0003767660370000191
  • Figure GDA0003767660370000201
    Figure GDA0003767660370000201
Patent Text Reader

Abstract

The object of the present invention is to provide a thermoplastic resin composition that exhibits high transmittance, low haze, excellent transparency, and excellent scratch resistance and toughness. The thermoplastic resin composition of the present invention is characterized in that it contains: 50 to 99% by mass of a methacrylic resin (A) composed of 80.0 to 99.9% by mass of a methacrylic acid ester monomer unit, 0.1 to 20.0% by mass of a vinyl monomer unit composed of a vinyl monomer copolymerizable with a methacrylic acid ester monomer other than maleic acid and maleic anhydride, and 0 to 4.0% by mass of a maleic acid and / or maleic anhydride monomer unit; and 1 to 50% by mass of a thermoplastic polyurethane (B) having a structural unit derived from a polyester polyol and a structural unit derived from an isocyanate having an alicyclic ring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermoplastic resin composition. Background Art

[0002] Methacrylic resins are transparent resins that have higher light transmittance, weather resistance, and rigidity than other plastic transparent resins, and have been used in a wide range of applications, such as vehicle parts, lighting equipment, building materials, signs, nameplates, paintings, and windows for display devices. Among them, methacrylic resin compositions are widely used as design parts for home appliances / OA products and design parts for interior and exterior decoration of automobiles due to their excellent appearance. However, methacrylic resin compositions have problems such as low toughness and surface damage when used outdoors, and their use is often limited to molded articles with mechanical parts or used after being deformed, and when used outdoors.

[0003] In Patent Document 1, a method of using a multilayer (meth) acrylic rubber polymer is attempted to improve toughness. However, these compositions cause stress whitening. Stress whitening refers to the haze generated when subjected to bending stress. In addition, in these compositions, damage resistance is not improved and still exists as a problem.

[0004] In addition, as another method for improving toughness, in Patent Document 2, compounding with elastomers was studied, and a transparent low-temperature impact-resistant plastic mixture composed of thermoplastic plastic (TPU) and poly (meth) acrylate with improved impact resistance was recorded. According to Patent Document 2, these plastic mixtures not only show good impact resistance, high tensile elastic modulus and good weather resistance, but also show acceptable transparency. The plastic mixture uses thermoplastic polyurethane with aliphatic bonds. In Patent Document 2, it is shown that under the test conditions described, the mixture of poly (meth) acrylate with improved impact resistance and thermoplastic polyurethane with aliphatic bonds reaches a transmittance of 83%, while the total light transmittance is 83%, which is not enough to be a transparent material. In addition, the transparency of the material is not only affected by the total light transmittance, but also by the haze.

[0005] Patent Document 3 shows, as an improvement to insufficient transparency, a composition in which an aliphatic isocyanate of a specific structure exhibits high transmittance and low haze, and in particular exhibits low haze and high transparency. However, the haze of the composition shown in Patent Document 3 is not low enough, and there is still room for improvement in its use as a transparent material.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2003-183471;

[0009] Patent document 2: International Publication No. 2007 / 057242;

[0010] Patent Document 3: Japanese Patent Application Publication No. 2015-532345. Summary of the invention

[0011] Problems to be solved by the invention

[0012] An object of the present invention is to provide a thermoplastic resin composition which exhibits high transmittance, low haze, excellent transparency, and excellent scratch resistance and toughness.

[0013] Technical solutions to problems

[0014] That is, the present invention is as follows.

[0015] [1] A thermoplastic resin composition comprising: 50 to 99% by mass of a methacrylic resin (A) composed of 80.0 to 99.9% by mass of a methacrylic acid ester monomer unit, 0.1 to 20.0% by mass of a vinyl monomer unit composed of a vinyl monomer copolymerizable with a methacrylic acid ester monomer other than maleic acid and maleic anhydride, and 0 to 4.0% by mass of a maleic acid and / or maleic anhydride monomer unit; and 1 to 50% by mass of a thermoplastic polyurethane (B) having a structural unit derived from a polyester polyol and a structural unit derived from an isocyanate having an alicyclic ring.

[0016] [2] The thermoplastic resin composition according to [1], wherein the number of alicyclic rings in the structural unit derived from the isocyanate having an alicyclic ring is one.

[0017] [3] The thermoplastic resin composition according to [1] or [2], wherein the methacrylic resin (A) has a weight average molecular weight of 50,000 to 250,000 as measured by gel permeation chromatography (GPC).

[0018] [4] The thermoplastic resin composition according to any one of [1] to [3], wherein the amount of terminal unsaturated double bonds in the methacrylic resin (A) is 0.01 mol% or less.

[0019] [5] The thermoplastic resin composition according to any one of [1] to [4], wherein the vinyl monomer unit composed of a vinyl monomer copolymerizable with a methacrylate monomer other than maleic acid and maleic anhydride is an acrylate monomer unit.

[0020] [6] The thermoplastic resin composition according to any one of [1] to [5], wherein the methacrylic resin (A) is composed of 85 to 99.9% by mass of methacrylic acid ester monomer units and 0.1 to 15% by mass of acrylic acid ester monomer units.

[0021] [7] The thermoplastic resin composition as described in any one of [1] to [6], wherein the mass ratio of the structural unit derived from isocyanate having one alicyclic ring is 70 mass% or more relative to 100 mass% of the total mass of the structural unit derived from isocyanate contained in the thermoplastic polyurethane (B).

[0022] [8] A method for producing a thermoplastic resin composition according to any one of [1] to [7], characterized in that a methacrylic resin (A) and a thermoplastic polyurethane (B) are mixed at a temperature in the range of 200 to 260°C.

[0023] [9] A molded article comprising the thermoplastic resin composition according to any one of [1] to [7].

[0024]

[10] An injection-molded article comprising the thermoplastic resin composition according to any one of [1] to [7].

[0025]

[11] A method for producing an injection molded article, comprising molding the thermoplastic composition according to any one of [1] to [7] at a cylinder temperature of 200 to 260°C.

[0026] Effects of the Invention

[0027] The thermoplastic resin composition of the present invention exhibits high transmittance and low haze, and is excellent in transparency, scratch resistance and toughness. DETAILED DESCRIPTION

[0028] [Thermoplastic resin composition]

[0029] Relative to 100% by mass of the thermoplastic resin composition, the thermoplastic resin composition of the present embodiment contains 50 to 99% by mass of a methacrylic resin (A) and 1 to 50% by mass of a thermoplastic polyurethane (B). The methacrylic resin (A) is composed of 80.0 to 99.9% by mass of methacrylate monomer units, 0.1 to 20.0% by mass of vinyl monomer units composed of vinyl monomers copolymerizable with methacrylate monomers other than maleic acid and maleic anhydride, and 0 to 4.0% by mass of maleic acid and / or maleic anhydride monomer units. The thermoplastic polyurethane (B) has a structural unit derived from a polyester polyol and a structural unit derived from an isocyanate having an alicyclic ring. In this specification, unless otherwise specified, the total mass of all components of the thermoplastic resin composition is set to 100% by mass.

[0030] <Methacrylic resin (A)>

[0031] The methacrylic resin (A) may contain at least one methacrylic resin, and one methacrylic resin may be used alone, or two or more methacrylic resins may be used in combination.

[0032] The methacrylic resin (A) needs to be composed of 80.0 to 99.9% by mass of methacrylic acid ester monomer units, 0.1 to 20.0% by mass of vinyl monomer units composed of vinyl monomers copolymerizable with methacrylic acid ester monomers other than maleic acid and maleic anhydride, and 0 to 4.0% by mass of maleic acid and / or maleic anhydride monomer units, based on 100% by mass of the methacrylic acid resin.

[0033] When the content of the methacrylate monomer unit is 99.9% by mass or less, the resin can be prevented from decomposing during molding, and the generation of the methacrylate monomer as a volatile component or molding defects called silver streaks can be effectively prevented. In addition, when the methacrylate monomer unit is 80.0% by mass or more, the heat resistance usually required for the molded product can be ensured. With sufficient heat resistance, rigidity can also be ensured, and the strength usually required as a molded body can be ensured.

[0034] The methacrylic acid ester monomer constituting the methacrylic acid ester monomer unit contained in the methacrylic acid resin (A) is not limited to the following substances, and examples thereof include butyl methacrylate, ethyl methacrylate, methyl methacrylate, propyl methacrylate, isopropyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, methacrylic acid (2-ethylhexyl), methacrylic acid (tert-butylcyclohexyl), benzyl methacrylate, methacrylic acid (2,2,2-trifluoroethyl), etc. Among them, methyl methacrylate and ethyl methacrylate are preferred from the viewpoint of easy availability and price.

[0035] The above-mentioned methacrylate monomers may be used alone or in combination of two or more.

[0036] The content of the methacrylic acid ester monomer unit relative to 100% by mass of the methacrylic resin (A) is preferably 85.0 to 99.9% by mass, more preferably 85.0 to 99.8% by mass, further preferably 85.0 to 99.5% by mass, further preferably 90.0 to 99.5% by mass, further more preferably 93.0 to 99.5% by mass, and particularly preferably 95.5 to 99.0% by mass from the viewpoint of simultaneously achieving higher transmittance and lower haze.

[0037] The vinyl monomer copolymerizable with the methacrylate monomer constituting the vinyl monomer unit contained in the methacrylic resin (A) is a vinyl monomer other than maleic acid and maleic anhydride, and is not limited to the following substances, for example, acrylate monomers having one acrylate group such as methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, and 2-ethylhexyl acrylate can be cited.

[0038] In addition, examples include esters obtained by esterifying both terminal hydroxyl groups of ethylene glycol or its oligomers with acrylic acid or methacrylic acid, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate, which have two or more (meth)acrylate groups; esters obtained by esterifying the hydroxyl groups of two alcohols with acrylic acid or methacrylic acid, such as neopentyl glycol di(meth)acrylate and di(meth)acrylate; esters obtained by esterifying polyol derivatives such as trimethylolpropane and pentaerythritol with acrylic acid or methacrylic acid; and the like acrylic acid ester monomers.

[0039] In particular, methyl acrylate, ethyl acrylate, and n-butyl acrylate are preferred, and methyl acrylate and ethyl acrylate are further preferred from the viewpoint of easy availability.

[0040] The vinyl monomer (preferably an acrylic acid ester monomer) copolymerizable with the methacrylic acid ester monomer may be used alone or in combination of two or more.

[0041] The content of the vinyl monomer unit composed of the above-mentioned vinyl monomer copolymerizable with the methacrylate monomer (preferably the content of the acrylate monomer) relative to 100% by mass of the methacrylic resin (A) needs to be 0.1 to 20.0% by mass, preferably 0.1 to 15.0% by mass, more preferably 0.2 to 15.0% by mass, and further preferably 0.5 to 7.0% by mass. From the viewpoint of simultaneously obtaining a higher transmittance and a lower haze, it is particularly preferably 1.0 to 6.5% by mass. By making the above-mentioned content 0.1% by mass or more, it is possible to prevent the decomposition of the methacrylic resin during molding or the decomposition of the thermoplastic polyurethane caused by the free radicals generated by the decomposition of the methacrylic resin or the deterioration caused by yellowing, and it is possible to effectively prevent the yellowing of the thermoplastic resin composition or the occurrence of poor molding due to the generation of volatile components. In addition, by making the vinyl monomer unit 20.0% or less by mass, it is possible to ensure the heat resistance usually required for the molded product.

[0042] In addition, from the viewpoint of ensuring fluidity during injection molding or maintaining transparency, the content of the vinyl monomer unit is preferably 0.4% by mass or less relative to the methacrylic resin (A) (100% by mass), particularly when a monomer having two (meth)acrylate groups is used, 0.25% by mass or less when a monomer having three (meth)acrylate groups is used, and 0.15% by mass or less when a monomer having four or more (meth)acrylate groups is used.

[0043] In addition, as other vinyl monomers other than maleic acid and maleic anhydride that can be copolymerized with the above-mentioned methacrylate monomer, other than the acrylate monomer, it is not limited to the following substances, for example, α, β-unsaturated acids such as acrylic acid or methacrylic acid; unsaturated group-containing dicarboxylic acids such as fumaric acid, itaconic acid, and cinnamic acid and their alkyl esters; styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, isopropenylbenzene (α -methylstyrene) and other styrene monomers; aromatic vinyl compounds such as 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, and isopropenyloctylbenzene; cyanide vinyl compounds such as acrylonitrile and methacrylonitrile; unsaturated carboxylic acid anhydrides such as itaconic anhydride; N-substituted maleimides such as maleimide, N-methylmaleimide, N-ethylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide; amides such as acrylamide and methacrylamide; multifunctional monomers such as divinylbenzene, etc.

[0044] The methacrylic resin (A) may optionally contain maleic acid and / or maleic anhydride monomer units.

[0045] Maleic acid and maleic anhydride can be copolymerized with methacrylate monomers, but they should not be used in excess from the viewpoint of preventing yellow tint when a thermoplastic resin composition is prepared with thermoplastic polyurethane or yellowing during molding, preventing silver streaks from occurring, and maintaining good weather resistance. Therefore, the content of maleic acid monomer units and / or maleic anhydride monomer units is preferably 0 to 4.0% by mass, more preferably 3.0% by mass or less, and even more preferably 2.0% by mass or less, relative to 100% by mass of the methacrylic resin (A). They may not be contained.

[0046] It should be noted that, in the methacrylic resin (A), a vinyl monomer other than the vinyl monomers listed above may be appropriately added for copolymerization in order to improve properties such as heat resistance and molding processability. The acrylic ester monomers copolymerizable with the methacrylic ester monomers or the vinyl monomers other than the acrylic ester monomers listed above may be used alone or in combination of two or more.

[0047] The total content by mass ratio of the methacrylate monomer units and the acrylate monomer units in 100 mass % of the methacrylic resin (A) is preferably 88 mass % or more, more preferably 94 mass % or more, and even more preferably 100 mass % from the viewpoint of obtaining a molded product having better transparency and haze.

[0048] The content of the methacrylic resin (A) in the thermoplastic resin composition of the present embodiment may be 50 to 99% by mass relative to 100% by mass of the thermoplastic resin composition. From the viewpoint of obtaining a molded body having excellent transparency and toughness, the content is preferably 50 to 95% by mass, more preferably 55 to 95% by mass, and even more preferably 60 to 90% by mass. From the viewpoint of obtaining a molded body having excellent transparency, toughness, and scratch resistance, the content is even more preferably 66 to 89% by mass, and particularly preferably 71 to 88% by mass.

[0049] (Weight average molecular weight)

[0050] The weight average molecular weight (Mw) of the methacrylic resin (A) contained in the methacrylic resin composition of the present embodiment will be described.

[0051] The weight average molecular weight (Mw) of the methacrylic resin (A) measured by GPC (gel permeation chromatography) is preferably 50,000 to 250,000.

[0052] In order to obtain good mechanical strength and solvent resistance when forming a thermoplastic resin composition, the lower limit of the weight average molecular weight (Mw) of the methacrylic resin (A) is preferably 50,000 or more, more preferably 70,000 or more, and further preferably 85,000 or more.

[0053] In order to make the methacrylic resin composition exhibit good fluidity, the upper limit of the weight average molecular weight (Mw) of the methacrylic resin (A) is preferably 250,000 or less, more preferably 230,000 or less, and further preferably 190,000 or less.

[0054] When the weight average molecular weight (Mw) of the methacrylic resin (A) is within the range of 50,000 to 250,000, the flowability, mechanical strength and solvent resistance of the thermoplastic resin composition can be balanced, and good molding processability can be maintained.

[0055] (Molecular weight distribution)

[0056] The molecular weight distribution (Mw / Mn) of the methacrylic resin (A) contained in the methacrylic resin composition of the present embodiment is preferably 1.0 to 6.0, more preferably 1.0 to 5.5, further preferably 1.0 to 5.0, and particularly preferably 1.01 to 1.96 from the viewpoint of further improving moldability. When the molecular weight distribution (Mw / Mn) of the methacrylic resin (A) is 1.0 to 6.0, the physical properties exhibited by the methacrylic resin (A) are stable.

[0057] Here, Mw represents a weight average molecular weight, and Mn represents a number average molecular weight.

[0058] The weight average molecular weight (Mw) and the number average molecular weight (Mn) of the methacrylic resin (A) can be measured by GPC, and specifically, can be measured by the method described in Examples described later.

[0059] Specifically, a standard methacrylic resin with a monodisperse, known weight average molecular weight and available as a reagent and an analytical gel column that allows high molecular weight components to be eluted first are used in advance, and a calibration curve is established based on the elution time and weight average molecular weight. Next, based on the obtained calibration curve, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin (A) as the specified measurement object can be obtained, and the molecular weight distribution (Mw / Mn) can be calculated. The number average molecular weight (Mn) refers to the average value of the molecular weight of each simple molecule, and is defined by the total weight of the system / the number of molecules in the system. The weight average molecular weight (Mw) is defined by the average value of the molecular weight using the weight fraction.

[0060] (Unsaturated double bond terminal amount)

[0061] In order to effectively prevent yellowing of the thermoplastic resin composition caused by decomposition or degradation of the thermoplastic polyurethane (B) in the thermoplastic resin composition of the present embodiment due to free radicals generated by the decomposition of the methacrylic resin (A) or molding defects caused by monomers generated by the decomposition of the thermoplastic resin composition, the amount of unsaturated double bonds at the terminals of the methacrylic resin (A) is preferably 0.01 mol% or less, more preferably 0.009 mol% or less, and even more preferably 0.008 mol% or less.

[0062] The amount of unsaturated double bond terminals can be controlled by controlling the polymerization temperature or using a chain transfer agent. In order to reduce the amount of unsaturated double bond terminals, specifically, in the case of manufacturing methacrylic resin (A) by suspension polymerization, the polymerization temperature is preferably set to 80°C or less, more preferably to 75°C or less, and further preferably to 70°C or less. The polymerization temperature may be constant, but setting the polymerization temperature to 70°C or less in the initial stage of polymerization is also effective for reducing the amount of unsaturated double bond terminals. In the polymerization initiator, relative to 100% by mass of methacrylic resin (A), it is preferably manufactured in an amount of 0.5% by mass or less of the polymerization initiator, more preferably 0.3% by mass or less, further preferably 0.25% by mass or less, and particularly preferably 0.23% by mass or less. In the case of manufacturing by solution polymerization, the polymerization temperature is preferably set to 185°C or less, more preferably 180°C or less, further preferably 170°C or less, and particularly preferably 160°C or less. The polymerization initiator is preferably produced in an amount of 0.4 mass % or less, more preferably 0.2 mass % or less, further preferably 0.15 mass % or less, particularly preferably 0.1 mass % or less, based on 100 mass % of the methacrylic resin (A).

[0063] In addition, the unsaturated double bond terminal amount can be measured by the method described in Examples mentioned later.

[0064] (Method for producing methacrylic resin (A))

[0065] The methacrylic resin (A) contained in the methacrylic resin composition of the present embodiment can be produced by solution polymerization, bulk polymerization, cast polymerization, or suspension polymerization, but is not limited to these methods. Bulk polymerization, solution polymerization, or suspension polymerization is preferred.

[0066] As for the polymerization temperature, it is sufficient to appropriately select the optimal polymerization temperature according to the polymerization method, preferably 50°C or more and 185°C or less, more preferably 50°C or more and 180°C or less, and further preferably 60°C or more and 170°C or less. By setting the polymerization temperature to 185°C or less, the amount of unsaturated double bond terminals can be reduced, and yellowing or poor molding of the thermoplastic resin composition caused by deterioration of the thermoplastic polyurethane (B) can be effectively prevented. In addition, by setting the polymerization temperature to 50°C or more, the methacrylic resin can be produced with good productivity.

[0067] When producing the methacrylic resin (A), a polymerization initiator may be used. The polymerization initiator is not limited to the following substances. In the case of free radical polymerization, for example, organic peroxides such as di-tert-butyl peroxide, lauroyl peroxide, stearoyl peroxide, benzoyl peroxide, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, dilauroyl peroxide, dicumyl peroxide, tert-butylperoxy-2-ethylhexanoate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and 1,1-bis(tert-butylperoxy)cyclohexane; and common azo-based free radical polymerization initiators such as azobisisobutyronitrile, azobisisovaleronitrile, 1,1-azobis(1-cyclohexanecarbonitrile), 2,2'-azobis-4-methoxy-2,4-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, and 2,2'-azobis-2-methylbutyronitrile can be mentioned. These may be used alone or in combination of two or more. These radical polymerization initiators may be used in combination with an appropriate reducing agent as a redox initiator.

[0068] These radical polymerization initiators and / or redox initiators are usually used in an amount within a range of 0 to 1 part by mass based on 100 parts by mass of the total amount of all monomers used in the polymerization of the methacrylic resin (A), and can be appropriately selected in consideration of the polymerization temperature and the half-life of the polymerization initiator.

[0069] When bulk polymerization, cast polymerization or suspension polymerization is selected as the polymerization method for the methacrylic resin (A), it is preferred to perform the polymerization using a peroxide polymerization initiator from the viewpoint of preventing coloration of the methacrylic resin (A).

[0070] The peroxide polymerization initiator is not limited to the following, and examples thereof include lauroyl peroxide, decanoyl peroxide, and t-butylperoxy-2-ethylhexanoate, and lauroyl peroxide is more preferred.

[0071] When the methacrylic resin (A) is polymerized by solution polymerization at a high temperature of 90°C or higher, it is preferred to use a peroxide, azo diinitiator or the like having a 10-hour half-life temperature of 80°C or higher and being soluble in the organic solvent used as a polymerization initiator.

[0072] The peroxide and azo diinitiator are not limited to the following substances, and examples thereof include 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, cyclohexane peroxide, 2,5-dimethyl-2,5-di(peroxybenzoyl)hexane, 1,1-azobis(1-cyclohexanecarbonitrile), and 2-(carbamoylazo)isobutyronitrile.

[0073] When producing the methacrylic resin (A), the molecular weight of the methacrylic resin (A) may be controlled within the range not impairing the purpose of the present invention. The method of controlling the molecular weight of the methacrylic resin (A) is not limited to the following, and for example, a method of controlling the molecular weight by using a chain transfer agent such as alkyl mercaptans, dimethylacetamide, dimethylformamide, triethylamine, or a dithiocarbamate, triphenylmethylazobenzene, tetraphenylethane derivative, or other iniferters may be cited. In addition, the molecular weight may be adjusted by adjusting the amount of these added.

[0074] As the chain transfer agent, alkyl mercaptans are preferred from the viewpoint of operability and stability. The alkyl mercaptans are not limited to the following substances, and examples thereof include n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, n-tetradecyl mercaptan, n-octadecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dimercaptoacetate, trimethylolpropane tris(thioglycolate), and pentaerythritol tetrakis(thioglycolate).

[0075] These substances can be appropriately added depending on the molecular weight of the target methacrylic resin, but are usually used in an amount within a range of 0.001 to 5 parts by mass based on 100 parts by mass of the total amount of all monomers used in the polymerization of the methacrylic resin.

[0076] Other molecular weight control methods include a method of changing the polymerization method, a method of adjusting the amount of the polymerization initiator, the chain transfer agent or the iniferter, and a method of changing various polymerization conditions such as the polymerization temperature.

[0077] Among these molecular weight control methods, only one method may be used, or two or more methods may be used in combination.

[0078] <Thermoplastic polyurethane (B)>

[0079] In the present embodiment, a thermoplastic polyurethane (B) is contained in the thermoplastic resin composition. The thermoplastic polyurethane (B) contains a structural unit derived from a polyester polyol and a structural unit derived from an isocyanate having an alicyclic ring. In order to make the transparency of the thermoplastic resin composition good, when all structural units derived from isocyanates are set to 100% by mass, the structural unit derived from an isocyanate having an alicyclic ring is preferably 70% by mass or more. When all structural units derived from isocyanates are set to 100% by mass, the structural unit derived from an isocyanate having an alicyclic ring is more preferably 75% by mass or more, further preferably 80% by mass or more, further more preferably 90% by mass or more, and particularly preferably 100% by mass.

[0080] The thermoplastic polyurethane (B) may be at least one type of thermoplastic polyurethane, and may be used alone or in combination of two or more types.

[0081] Usually, thermoplastic polyurethane is produced by reacting the following components: (a) isocyanate, (b) a compound reactive to isocyanate and optionally at least one (c) catalyst and / or (d) conventional auxiliary agent and / or additive. The following components: (a) isocyanate and (b) a compound reactive to isocyanate are referred to as structural components. The method for identifying these structural components is not limited to the conventionally known methods such as the following method, and the method described in the Journal of the Japanese Society of Adhesion Vol. 40 No. 6 (2004) can be cited.

[0082] As (a) isocyanate, from the perspective of transparency (high total light transmittance and low haze) and damage resistance of the thermoplastic resin composition, it is preferred to use an isocyanate with an alicyclic ring in the structure, and it is more preferred to use an isocyanate without unsaturated carbon bonds, aromatic rings but with an alicyclic ring. It is not limited to the following substances, specifically, from the perspective of damage resistance and transparency being more excellent, preferably 4,4-diisocyanate dicyclohexylmethane (H12MDI), 1,3-diisocyanato methylcyclohexane (XDI), isophorone diisocyanate (IPDI), more preferably 1,3-diisocyanato methylcyclohexane (XDI), isophorone diisocyanate (IPDI). In the range of not damaging the effect of the present invention, isocyanate can be an isocyanate having a mixture or additive of 5% by mass or less in isocyanate.

[0083] The number of alicyclic rings contained in the (a) isocyanate is preferably 1 to 4, and more preferably 1 in order to improve the heat deformation resistance, transparency of the thermoplastic resin composition, and yellowing resistance during thermal processing.

[0084] When the isocyanate (a) contains a plurality of isocyanates having alicyclic rings, the number of alicyclic rings may be the number of alicyclic rings of the compound having the largest molar fraction among the compounds contained in the isocyanate (a).

[0085] As (b) a compound reactive to isocyanate, at least one polyester polyol can be cited. By using polyester polyol, the transparency of the thermoplastic resin composition is good. In the present invention, the structure of the thermoplastic polyurethane (B) needs to contain a structural unit derived from polyester polyol or a mixture of two or more thereof. It should be noted that the polyester polyol contains polycarbonate diol.

[0086] The mass ratio of the structural unit derived from the polyester polyol in 100 mass % of the structural unit derived from the polyol contained in the thermoplastic polyurethane (B) is preferably 80 to 100 mass %, more preferably 90 to 100 mass %, and even more preferably 95 to 100 mass %.

[0087] The mass proportion of the structural unit derived from polyether in 100 mass % of the structural units derived from polyol contained in the thermoplastic polyurethane (B) is preferably less than 5 mass %, more preferably less than 2 mass %, further preferably less than 1 mass %, and particularly preferably not contained.

[0088] Examples of the polyester polyol include polyester polyols produced from organic dicarboxylic acids having 2 to 12 carbon atoms (preferably aromatic dicarboxylic acids having 8 to 12 carbon atoms) and polyols (preferably diols having 2 to 12 carbon atoms, more preferably diols having 2 to 6 carbon atoms).

[0089] As the above-mentioned organic dicarboxylic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, decanedicarboxylic acid, maleic acid, fumaric acid, phthalic acid, isophthalic acid, terephthalic acid, isomers of naphthalene dicarboxylic acid can be mentioned. The dicarboxylic acid can be used in any form of a monomer or a mixture with other dicarboxylic acids. It is also possible to use the corresponding dicarboxylic acid derivatives instead of free dicarboxylic acids, for example, dicarboxylic acid esters or dicarboxylic acid anhydrides of alcohols having 1 to 4 carbon atoms.

[0090] As the above-mentioned polyol, diol is preferred. As the above-mentioned diol, ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, dipropylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,10-decanediol, glycerol, trimethylolpropane can be mentioned, preferably ethylene glycol, 1,3-propylene glycol, methyl-1,3-propanediol, 1,4-butylene glycol, 3-methyl-1,5-pentanediol or 1,6-hexanediol. As the above-mentioned polyol, polyester diols made from lactones (e.g., ε-caprolactone) and hydroxycarboxylic acids (e.g., ω-hydroxycarboxylic acids, hydroxybenzoic acid) can be used.

[0091] In the production of polyester polyol, the reaction conditions of the organic dicarboxylic acid and the polyol can be selected so that the produced polyester polyol does not have a free acid group. The actual number of functional groups of the produced polyester polyol is preferably 1.9 to 2.1, more preferably 2.0.

[0092] In the production of polyester polyol, a mixture of an organic dicarboxylic acid and a polyol may be polycondensed in the presence or absence of a catalyst. Among them, the reaction in the presence of a catalyst is preferred, and the reaction in the presence of an esterification catalyst is more preferred.

[0093] In the production of polyester polyol, a mixture of an organic dicarboxylic acid and a polyol may be polycondensed in an atmosphere of an inert gas (for example, nitrogen, carbon monoxide, helium, argon, or the like).

[0094] The temperature during the polycondensation of the organic dicarboxylic acid and the polyol is preferably 150 to 250° C., more preferably 180 to 220° C. The polycondensation may be performed under reduced pressure as desired.

[0095] Usually, the above-mentioned polycondensation is continuously carried out until a desired acid value (for example, an acid value of less than 10, preferably an acid value of less than 2) is reached.

[0096] The molar ratio of the organic dicarboxylic acid to the polyol used in the polycondensation is preferably 1:1 to 1.8, more preferably 1:1.05 to 1.2.

[0097] In particular, it is preferred that the thermoplastic polyurethane (B) contains a structural unit derived from a polyester polyol produced from ε-caprolactone and / or a structural unit derived from a condensate of adipic acid or sebacic acid and at least one polyol selected from the group consisting of ethylene glycol, 1,3-propylene glycol, methyl-1,3-propanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol and 1,6-hexanediol.

[0098] The number average molecular weight Mn of the polyester polyol used is preferably 500 to 4,000, more preferably 650 to 3,500, and even more preferably 800 to 3,000.

[0099] In addition, the number average molecular weight Mn can be measured by the GPC method.

[0100] As (b) a compound reactive with isocyanate, polyols may be mentioned in addition to polyester polyols. Among the polyols, at least one polyol selected from the group consisting of 1,2-ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol and neopentyl glycol is preferred. More preferably, a polyol selected from the group consisting of 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol and 1,6-hexanediol is preferred. The polyol functions as a chain extender.

[0101] In the thermoplastic resin composition of the present embodiment, the thermoplastic polyurethane (B) preferably contains a structural unit derived from at least one polyol selected from the group consisting of 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butanediol and 1,6-hexanediol.

[0102] As the above-mentioned (c) catalyst, it is preferred that the (c) catalyst accelerates the reaction between the NCO group of (a) isocyanate and the hydroxyl group of (b) the compound reactive to isocyanate. As the above-mentioned (c) catalyst, tertiary amines can be mentioned, preferably triethylamine, dimethylcyclohexylamine, N-methylmorpholine, N,N'-dimethylpiperazine, 2-(dimethylaminoethoxy)ethanol or diazabicyclo[2.2.2]octane. In addition, as the above-mentioned (c) catalyst, it is preferred that an organic metal compound (for example, a titanate, an iron compound (preferably iron (III) acetylacetonate), a tin compound (preferably tin diacetate, tin dioctoate, tin dilaurate) or a dialkyltin salt of an aliphatic carboxylic acid (preferably dibutyltin diacetate, dibutyltin dilaurate), bismuth preferably exists in the oxidation state of 2 or 3, especially 3).

[0103] As the above-mentioned (c) catalyst, a carboxylate is preferred. As the above-mentioned carboxylic acid, a carboxylic acid having 6 to 14 hydrocarbons is preferred, and a carboxylic acid having 8 to 12 hydrocarbons is particularly preferred. As the carboxylate, a bismuth salt is preferred, and examples of preferred bismuth salts include bismuth (III) neodecanoate, bismuth 2-ethylhexanoate, and bismuth octanoate.

[0104] As the catalyst (c) used in the manufacture of thermoplastic polyurethane (B), a tin catalyst, particularly tin dioctoate, is preferably used, and as a mass ratio, it is preferably 0.0001 to 0.1 mass parts relative to 100 mass parts of the compound (b) reactive to isocyanate. When a tertiary amine is used as the catalyst (c), from the viewpoint of preventing the tertiary amine from being mixed into the structural skeleton of the thermoplastic polyurethane (B) and causing yellowing during the molding of the thermoplastic resin composition, the tertiary amine content in 100 mass% of the thermoplastic resin composition of the present embodiment is preferably 0.9 mass% or less, more preferably 0.5 mass% or less, further preferably 0.1 mass% or less, and particularly preferably 0 mass%. In addition, from the viewpoint of preventing yellowing during the molding, the tertiary amine content contained in 100 mass% of the above-mentioned thermoplastic polyurethane (B) is preferably 0.9 mass% or less, more preferably 0.5 mass% or less, further preferably 0.1 mass% or less, and particularly preferably 0 mass%.

[0105] As the ratio of the structural components (a) and (b) when producing the thermoplastic polyurethane (B), the equivalent ratio of the NCO group of the isocyanate (a) to the total hydroxyl group of the structural component (b) is preferably 0.9 to 1.1:1, more preferably 0.95 to 1.05:1, and further preferably 0.96 to 1.0:1. For the production of the thermoplastic polyurethane (B), the reaction is preferably carried out in the presence of a catalyst (c) and optionally an auxiliary agent and / or an additive (d).

[0106] The content of the thermoplastic polyurethane (B) in the thermoplastic resin composition of the present embodiment is 1 to 50% by mass relative to 100% by mass of the thermoplastic resin composition. From the viewpoint of obtaining a molded product having good toughness and transparency, the content is preferably 5 to 50% by mass, more preferably 5 to 45% by mass, and even more preferably 10 to 40% by mass. From the viewpoint of obtaining a molded product having good toughness, transparency and scratch resistance, the content is even more preferably 11 to 34% by mass, and particularly preferably 12 to 29% by mass.

[0107] The total content of the methacrylic resin (A) and the thermoplastic polyurethane (B) in the thermoplastic resin composition of the present embodiment is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass, based on 100% by mass of the thermoplastic resin composition.

[0108] <Other ingredients>

[0109] The thermoplastic resin composition of the present embodiment may contain other components in addition to the methacrylic resin (A) and the thermoplastic polyurethane (B) as long as the effects of the present invention are not impaired. As the other components, other conventionally known resins may be mixed.

[0110] The other resin is not particularly limited, and a known curable resin or thermoplastic resin is preferably used.

[0111] Thermoplastic resins are not limited to the following substances, and examples thereof include polypropylene resins, polyethylene resins, polystyrene resins, syndiotactic polystyrene resins, ABS resins, methacrylic resins, AS resins, BAAS resins, MBS resins, AAS resins, biodegradable resins, alloys of polycarbonate-ABS resins, polybutylene terephthalate, polyethylene terephthalate, polytrimethylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate and other polyalkylene aromatic ester resins, polyamide resins, polyphenylene ether resins, polyphenylene sulfide resins, phenolic resins, and the like.

[0112] In particular, AS resin and BAAS resin are preferred in order to improve fluidity, ABS resin and MBS resin are preferred in order to improve impact resistance, and polyester resin is preferred in order to improve chemical resistance.

[0113] In addition, polyphenylene ether resins, polyphenylene sulfide resins, phenolic resins, and the like can achieve the effect of improving flame retardancy.

[0114] In addition, the curable resin is not limited to the following substances, for example, unsaturated polyester resin, vinyl ester resin, diallyl phthalate resin, epoxy resin, cyanate resin, xylene resin, triazine resin, urea-formaldehyde resin, melamine resin, benzoguanamine resin, polyurethane resin, oxetane resin, ketone resin, alkyd resin, furan resin, styrene pyridine resin, silicone resin, synthetic rubber, etc.

[0115] These resins may be used alone or in combination of two or more.

[0116] The thermoplastic resin composition of the present embodiment may contain various additives other than the methacrylic resin (A) and the thermoplastic polyurethane (B) in order to impart various predetermined properties such as rigidity and dimensional stability, within a range not impairing the effects of the present invention.

[0117] The additives are not limited to the following substances, for example, plasticizers such as phthalate esters, fatty acid esters, trimellitate esters, phosphate esters, polyesters, etc.; mold release agents such as higher fatty acids, higher fatty acid esters, higher fatty acid monoglycerides, diglycerides or triglycerides; antistatic agents such as polyethers, polyether esters, polyether ester amides, alkyl sulfonates, alkyl benzene sulfonates, etc.; stabilizers such as phosphine stabilizers and light stabilizers; flame retardants; flame retardant aids; curing agents; Curing accelerator; conductivity imparting agent; stress relaxation agent; crystallization accelerator; dye; hydrolysis inhibitor; lubricant; UV absorber; antioxidant; impact resistance imparting agent; slip improver; compatibilizer; nucleating agent; reinforcing agent; reinforcing agent; flow regulator; sensitizer; coloring pigment; rubber polymer; thickener; anti-settling agent; anti-sagging agent; filler; defoaming agent; coupling agent; rust inhibitor; antibacterial / mildewproof agent; antifouling agent; conductive polymer; carbon black, etc.

[0118] Impact resistance imparting agents such as acrylic rubber multilayer polymers are particularly preferred.

[0119] The content of the above-mentioned other components in the thermoplastic resin composition for obtaining the thermoplastic resin composition molded product of the present embodiment is preferably 0 to 40% by mass, more preferably 0.01 to 30% by mass, and further preferably 0.02 to 25% by mass relative to 100% by mass of the thermoplastic resin composition in order to maintain the transparency of the thermoplastic resin composition and prevent molding defects such as bleeding. By containing the above-mentioned range, the functions of various materials can be exerted.

[0120] In order to effectively impart impact resistance and ensure transparency, the impact resistance imparting agent is preferably contained in an amount of 3 to 50% by mass, more preferably 5 to 20% by mass, and even more preferably 5 to 9% by mass based on 100% by mass of the thermoplastic resin composition.

[0121] The thermoplastic resin composition according to the present embodiment has a total light transmittance of preferably 89% or more, more preferably 90% or more, and even more preferably 91% or more when prepared as a flat plate sample.

[0122] For example, the total light transmittance can be adjusted by setting the mass ratio of the methacrylic resin (A) to the thermoplastic polyurethane (B) to the preferred range, using the resin of the preferred example as the methacrylic resin (A), and the like.

[0123] It should be noted that the total light transmittance can be measured by the method described in Examples below.

[0124] The thermoplastic resin composition of the present embodiment preferably has a haze of 10% or less, more preferably 9% or less, further preferably 8% or less, and particularly preferably 3.5% or less when prepared as a flat plate sample.

[0125] For example, the haze can be adjusted by setting the mass ratio of the methacrylic resin (A) to the thermoplastic polyurethane (B) to the preferred range, using the resin of the preferred example as the methacrylic resin (A), and the like.

[0126] In addition, the said haze can be measured by the method described in the Example mentioned later.

[0127] <Method for producing thermoplastic resin composition>

[0128] The thermoplastic resin composition is obtained by mixing and kneading the methacrylic resin (A) and the thermoplastic polyurethane (B), and, if necessary, the above-mentioned various additives and other resins.

[0129] For example, the polyol can be produced by kneading using a kneading machine such as an extruder, a heating roll, a kneader, a tumble mixer, or a Banbury mixer.

[0130] In particular, kneading using an extruder is preferred from the viewpoint of productivity.

[0131] From the viewpoint of productivity, the kneading temperature (i.e., the temperature when the methacrylic resin (A) and the thermoplastic polyurethane (B) are mixed) is preferably 170° C. or higher, more preferably 180° C. or higher, and further preferably 200° C. or higher. From the viewpoint of preventing the degradation of the methacrylic resin (A) or the thermoplastic polyurethane (B) and the volatilization of various additives, it is preferably 290° C. or lower, more preferably 280° C. or lower, and further preferably 260° C. or lower. When an extruder is used, the kneading temperature in this embodiment refers to the set temperature of the center of the cylinder.

[0132] <Molding body>

[0133] The molded article of the present embodiment is characterized by comprising the thermoplastic resin composition of the present embodiment. The molded article may be an injection molded article.

[0134] <Method for producing molded article>

[0135] The molded body of the present embodiment can be manufactured by a known molding method. Known molding methods are not limited to the following materials, for example, injection molding, extrusion molding, blow molding (hollow) molding, vacuum molding, compression molding, calendering molding, inflation molding, etc. can be cited. In particular, from the viewpoint of productivity, it is preferably molded by injection molding.

[0136] From the viewpoint of productivity, the molding temperature is preferably 170° C. or higher, more preferably 190° C. or higher, and even more preferably 200° C. or higher. From the viewpoint of preventing the degradation of the methacrylic resin (A) or the thermoplastic polyurethane (B) and the volatilization of various additives, the molding temperature is preferably 290° C. or lower, more preferably 280° C. or lower, and even more preferably 260° C. or lower.

[0137] In addition, the cylinder temperature during molding is preferably 170° C. or higher, more preferably 190° C. or higher, and even more preferably 200° C. or higher from the viewpoint of productivity. In addition, in order to prevent the degradation of the methacrylic resin (A) or the thermoplastic polyurethane (B) and the volatilization of various additives, it is preferably 290° C. or lower, more preferably 280° C. or lower, and even more preferably 260° C. or lower.

[0138] <Application of Molded Article>

[0139] The molded body of the thermoplastic resin composition of the present embodiment has good weather resistance, damage resistance and transparency. In addition, since a resin molded body with excellent long-term stability in an outdoor environment exposed to ultraviolet rays can be obtained, it can be applied to plastic greenhouse films, liquid crystal protective films, building components, vehicle components, electrical and electronic components, lighting components, etc. As the purpose of the molded body of the present embodiment, specifically, for example, roofing materials, lighting or signs for buildings, cars, trains or buses, protective materials for instruments, vehicle lamp components, ship lamp components, battery protection covers, etc. It is particularly preferably used as a vehicle component and a vehicle lamp component.

[0140] Other embodiments of the present invention can be learned from the claims and examples. The above-mentioned features of the article, manufacturing method, and method of use of the present invention and the features described below are of course not just the combinations described separately, but other combinations can also be used as long as they do not exceed the scope of the present invention. Therefore, for example, although the present invention does not explicitly describe the combination, it also implies the combination of preferred features with particularly preferred features or the combination of features that are not described in detail with particularly preferred features.

[0141] Example

[0142] The following are examples of the present invention, but these do not limit the present invention. In particular, the present invention also includes embodiments derived from these combinations.

[0143] [Raw materials used in Examples and Comparative Examples]

[0144] <Raw materials of methacrylic resin (A)>

[0145] The raw materials of the methacrylic resin (A) used for producing the thermoplastic resin composition are as follows.

[0146] Methyl methacrylate (MMA): manufactured by Asahi Kasei (2.5 ppm by mass of 2,4-dimethyl-6-tert-butylphenol manufactured by Chugai Trade was added as a polymerization inhibitor).

[0147] Methyl acrylate (MA): manufactured by Mitsubishi Chemical (14 ppm by mass of 4-methoxyphenol manufactured by Kawaguchi Chemical Industries, Ltd. was added as a polymerization inhibitor).

[0148] · Ethyl acrylate (EA): manufactured by Mitsubishi Chemical.

[0149] Maleic anhydride (MAH): manufactured by Nippon Shokubai Co., Ltd.

[0150] · n-Octyl mercaptan: manufactured by Arkema.

[0151] ·Lauroyl peroxide: Made by NOF.

[0152] Perhexa 22: Made by NOF.

[0153] · Meta-xylene: manufactured by Tokyo Chemical Industry Co., Ltd.

[0154] Tricalcium phosphate: Made by Nippon Chemical Industry, used as a suspending agent.

[0155] · Calcium carbonate: manufactured by Shiraishi Industries, used as a suspending agent.

[0156] Sodium laurel sulfate: manufactured by Wako Pure Chemical Industries, used as a suspending aid.

[0157] <Thermoplastic polyurethane (B)>

[0158] · Elastollan NY5685N00A: manufactured by FCI Co., Ltd., polyurethane 1.

[0159] · Elastollan XCT-A1095: manufactured by FCI Co., Ltd., polyurethane 2.

[0160] · Elastollan NY1385V3-10HB: manufactured by FCI Co., Ltd., polyurethane 3.

[0161] · Elastollan HD595A10: manufactured by FCI Co., Ltd., polyurethane 4.

[0162] Table 1

[0163]

[0164] <Additives>

[0165] Kane Ace M-210: Made by Kanebuchi, Japan, acrylic rubber impact resistance improver.

[0166] Tinuvin P: manufactured by BASF, melting point 128°C.

[0167] Stearyl alcohol: manufactured by Kao, KALCOL 8098.

[0168] [Measurement and evaluation methods]

[0169] <I. Measurement of Molecular Weight of Methacrylic Resin (A)>

[0170] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) (Mn is the number average molecular weight) of the methacrylic resin (A) were measured using the following apparatus and conditions.

[0171] · Measurement device: gel permeation chromatograph (HLC-8320GPC) manufactured by Tosoh Corporation;

[0172] ·Measurement conditions:

[0173] Columns: 1 TSKguard column SuperH-H, 2 TSKgel SuperHM-M, 1 TSKgelSuperH2500, used in series. In this column, high molecular weight elutes quickly, while low molecular weight elutes slowly;

[0174] Detector: RI (differential refractometer) detector;

[0175] Detection sensitivity: 3.0mV / min;

[0176] Column temperature: 40°C;

[0177] Sample: 20 mL of tetrahydrofuran solution of 0.02 g of methacrylic resin;

[0178] Injection volume: 10 μL;

[0179] Developing solvent: tetrahydrofuran, flow rate: 0.6 mL / min, 0.1 g / L of 2,6-di-tert-butyl-4-methylphenol (BHT) was added as an internal standard.

[0180] As standard samples for calibration curve, the following 10 types of polymethyl methacrylates having known monodisperse peak molecular weights and different molecular weights (manufactured by Polymer Laboratories; PMMA Calibration Kit MM-10) were used.

[0181] Note that, since polymethyl methacrylate used as a standard sample in the calibration curve standard sample is a single peak, the corresponding peak is recorded as the weight peak molecular weight Mp. In this regard, it is distinguished from the peak top molecular weight calculated when there are multiple peaks for one sample.

[0182]

[0183]

[0184] Under the above conditions, the RI detection intensity relative to the elution time of the methacrylic resin (A) was measured.

[0185] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the methacrylic resin (A) were determined based on the area of ​​the region in the GPC elution curve and the calibration curve of the cubic approximation.

[0186] <II. Analysis of structural units of methacrylic resin (A)>

[0187] pass 1 The structural unit was identified by H-NMR measurement, and its amount (mass %) was calculated.

[0188] 1 The measurement conditions of H-NMR measurement are as follows.

[0189] Device: JEOL-ECA500;

[0190] Solvent: CDCl3-d1 (deuterated chloroform);

[0191] Sample: 1 g of methacrylic resin (A) was dissolved in 10 mL of acetone, 20 mL of methanol was added dropwise and filtered, and 15 mg of the insoluble matter was vacuum dried at 40°C for 15 hours and dissolved in 0.75 mL of CDCl3-d1 to prepare a sample for measurement.

[0192] <III. Unsaturated double bond terminal amount of methacrylic resin (A)>

[0193] pass 1 The structural unit was identified by H-NMR measurement, and the amount (mol %) in the methacrylic resin (A) was calculated.

[0194] The amount of unsaturated double bond terminals was calculated from the integrated value of the unsaturated double bond terminal peak (5.4 to 5.6 ppm) and the integrated value of the peak of the methyl group bonded to the oxygen atom of the ester group of the methacrylic resin (A) (3.6 ppm).

[0195] 1 The measurement conditions of H-NMR measurement are as follows.

[0196] Device:JEOL-ECA500.

[0197] Number of scans: 5000 times.

[0198] Measurement temperature: room temperature.

[0199] Observed nucleus: 1H (500MHz).

[0200] Solvent: CDCl3-d1 (deuterated chloroform).

[0201] Sample: Dissolve 1 g of methacrylic resin (A) in 10 mL of chloroform, add 20 mL of methanol and filter. Dissolve the insoluble components after filtration in 10 mL of chloroform again, add 20 mL of methanol and filter, repeat twice. 75 mg of the remaining insoluble components were vacuum dried at 40°C for 15 hours and dissolved in 0.75 mL of CDCl3-d1 to prepare a sample for measurement. If the insoluble components after the final filtration do not reach 75 mg, repeat the above operation until 75 mg is reached.

[0202] <Measurement of total light transmittance>

[0203] The total light transmittance of the flat plate sample having a thickness of 2 mm obtained by the method described below was measured using NDH7000 manufactured by Nippon Denshoku Co., Ltd. in accordance with JIS K7361. A total light transmittance of 91% or more was recorded as "◎" (particularly excellent), 90% or more was recorded as "○" (good), 89% or more was recorded as "△" (level with no practical problems), and less than 89% was recorded as "×" (poor).

[0204] <Measurement of haze and scratch resistance>

[0205] A flat plate sample having a thickness of 2 mm obtained by the method described later and a reference white slide glass No. 001 manufactured by Matsunami Glass Co., Ltd. were placed so as not to move in the vertical direction relative to the ground. In contrast, 22 g of Quarzsand F36 manufactured by Quarzwerke GmbH, 512 g of water and a stirring bar were added to a spray gun having a nozzle diameter of 1.3 mm, and while stirring at a speed of 1000 rpm with a magnetic stirrer, the flat plate sample and the reference glass were placed and sprayed under the conditions of an injection pressure of 0.3 MPa, a flow rate of 0.24 L / min, and a distance between the nozzle and the sample of 19 cm so that Quarzsand F36 was in contact with the reference glass and the flat plate sample in the same manner.

[0206] The haze before and after the test was measured using NDH7000 manufactured by Nippon Denshoku in accordance with JIS K7136, and the change value was calculated to evaluate the scratch resistance. It should be noted that the haze was measured at the center of the test site where Quarzsand F36 was in contact. The test was terminated when the haze of the reference glass reached 3. If the haze of the reference glass did not reach 3 after one test, the test was repeated under the same conditions.

[0207] In the evaluation of the scratch resistance, a change in haze of 7% or less was evaluated as "○" (good), and a change in haze of more than 7% was evaluated as "×" (bad). The change in haze was calculated according to the following formula.

[0208] (Change in haze (%)) = (haze after test (%)) - (haze before test (%))

[0209] In addition, as the judgment of the haze, the haze before the test of a flat plate sample with a thickness of 2 mm obtained by the method described later was taken as the haze of the thermoplastic resin composition. If the haze value was 3% or less, it was recorded as "◎" (particularly excellent), if it was greater than 3% and less than 8%, it was recorded as "○" (excellent), if it was greater than 8% and less than 10%, it was recorded as "△" (a level with no practical problems), and if it was greater than 10%, it was recorded as "×" (poor).

[0210] <Evaluation of injection moldability>

[0211] A flat plate sample with a thickness of 2 mm was prepared by the method described below. When visually confirmed, if the appearance of the flat plate sample was defective or the particles were significantly yellowed, it was recorded as "△" (injection moldability has problems), and if there was no appearance defect, it was recorded as "○" (good). Based on this evaluation, it can be evaluated whether injection molding is preferred when the thermoplastic resin composition of the present embodiment is subjected to thermal processing.

[0212] <Evaluation of toughness>

[0213] The ISO dumbbell test piece obtained in the "ISO dumbbell test piece" described later was subjected to a tensile test according to ISO527-1. The test was performed using a universal testing machine AGS-5kNX manufactured by Shimadzu Corporation. The tensile failure strain or the tensile failure nominal strain was measured 5 times when the distance between the markings was 50 mm, and the average value was used as an indicator of toughness. When the tensile failure strain or the tensile failure nominal strain was 9% or more, it was recorded as "0" (excellent), and when it was less than 9%, it was recorded as "×" (poor).

[0214] <Evaluation of yellowing resistance>

[0215] The pellets of the thermoplastic resin composition are put into an injection molding machine (EC-100SX manufactured by Toshiba Machine) with the temperature of the central part of the cylinder set to 220°C and the mold temperature set to 50°C, and 6 100mm square flat plates with a thickness of 2mm are molded and discarded, and the yellowness of the 7th to 11th sheets is measured and the average value YI1 is calculated. The molding cycle at this time is 65 seconds. Next, the pellets are put into an injection molding machine (EC-100SX manufactured by Toshiba Machine) with the temperature of the central part of the cylinder set to 250°C and the mold temperature set to 50°C, and 6 100mm square flat plates with a thickness of 2mm are molded and discarded, and the yellowness of the 7th to 11th sheets is measured and the average value YI2 is calculated. The molding cycle at this time is 65 seconds.

[0216] ΔYI was calculated from YI2-YI1, and as an index of thermal stability, yellowing resistance was evaluated based on the criteria of ΔYI≤0.5: ◎ (excellent), 0.5<ΔYI<1.5: 0 (good), 1.5≤ΔYI≤2.0: △ (practically sufficient thermal stability), and ΔYI<2.0: × (poor). This evaluation revealed the difference in yellow tone with respect to the molding temperature conditions, and the degree of freedom in setting the molding conditions when the thermoplastic resin composition of the present embodiment is subjected to thermal processing can be evaluated.

[0217] In addition, the yellowness was measured by using a colorimeter TC-8600A manufactured by Tokyo Denshoku Co., Ltd. under a C light source and a 10° viewing field transmission mode.

[0218] <Evaluation of processing stability>

[0219] The pellets of the thermoplastic resin composition were put into an injection molding machine (EC-100SX manufactured by Toshiba Machine) with the cylinder center temperature set at 260°C, the mold temperature set at 50°C, the injection speed set at 30 mm / sec, and the molding cycle set at 65 sec, to mold 50 sheets of 100 mm square flat plates with a thickness of 2 mm. The number of sheets with silver streaks generated at this time was counted as an indicator of thermal processing stability.

[0220] The processing stability during hot working was evaluated based on the criteria that the number of silver streaks generated was ○ (good) when 3 or less, △ (practically sufficient level) when 7 or less, and × (poor) when 8 or more. Based on this evaluation, the continuous moldability (productivity) under relatively high molding temperature conditions when the thermoplastic resin composition of the present embodiment is hot worked can be evaluated.

[0221] The thermoplastic resin composition of the present embodiment can be analyzed by the following method for the mass ratio of the methacrylic resin (A) to the thermoplastic polyurethane (B) in the thermoplastic resin composition.

[0222] 400 mg of a thermoplastic resin composition is dissolved in 40 mL of tetrahydrofuran. The solution phase contains methacrylic resin (A), and the swelling layer contains thermoplastic polyurethane (B). The solution phase is separated by filtration, and the substance obtained by reprecipitation with 350 mL of methanol is dissolved again in 40 mL of tetrahydrofuran. The substance obtained by reprecipitation with 350 mL of methanol is dried and solidified at 60°C under a nitrogen flow to prepare sample A, and the mass is measured. A substance obtained by adding 2 mg of dimethyl sulfone standard substance as a standard substance to 10 mg of sample A is dissolved in 1 mL of CDCl3-d1 to prepare sample 1 for measurement. By 1 The mass of the methacrylic resin (A) in 10 mg of the sample A was quantified by H-NMR measurement (ECA-500 manufactured by JEOL Ltd.). The mass ratio of the methacrylic resin in 10 mg of the sample A was applied to the sample A to determine the mass ratio of the methacrylic resin in the thermoplastic resin composition. At this time, the structure of the methacrylic resin (A) can also be identified.

[0223] In addition, the mass of the swollen layer was measured by drying and solidifying the sample B at 60°C under a nitrogen stream. A sample 2 for measurement was prepared by adding 2 mg of a bistrimethylsilylbenzene-d4 standard substance to 10 mg of the sample B and dissolving it in 1 mL of deuterated dimethylformamide. 1H-NMR measurement (ECA-500 manufactured by JEOL Ltd.) was used to quantify the mass of the thermoplastic polyurethane (B) in 10 mg of sample B. The mass ratio of the thermoplastic polyurethane in 10 mg of sample B was applied to sample B to determine the mass ratio of the thermoplastic polyurethane (B) in the thermoplastic resin composition. At this time, the structure of the thermoplastic polyurethane (B) can also be identified.

[0224] In the case where the detailed composition of thermoplastic polyurethane (B) is unclear, the composition can also be identified by IR measurement or thermal decomposition GC / MS measurement. In the IR measurement, the frozen and crushed sample B is mixed with KBr and tableted, and then IR measurement is performed to identify the composition of thermoplastic polyurethane (B). In the thermal decomposition GC / MS measurement, 25.0 mg of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is collected in a volumetric flask with a capacity of 100 mL. Dimethylformamide is filled to the scale line of the volumetric flask to make a 0.025% by mass octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate standard solution. 1 mL of the standard solution is added to the sample B to dissolve it as a solution for thermal decomposition GC / MS measurement. For thermal decomposition GC / MS measurement, a double-click thermal cracker is used for thermal extraction at 300°C in the first stage, thermal decomposition at 500°C in the second stage, and thermal decomposition GC / MS measurement is performed to identify the composition of thermoplastic polyurethane (B).

[0225] In the thermoplastic resin composition of the present embodiment, the mass ratio of the tertiary amine contained in the thermoplastic resin composition can be measured by the following method.

[0226] 200 mg of the thermoplastic resin composition was freeze-pulverized and immersed in 10 mL of a 0.01 mol % hydrochloric acid aqueous solution for 3 hours. 0.05 mL of a phenolphthalein solution was added thereto, and neutralization titration was performed with a 0.01 mol % sodium hydroxide aqueous solution. The amount of hydrochloric acid consumed was calculated based on the titration amount as the tertiary amine content in the thermoplastic resin composition, and converted into the mass ratio of the tertiary amine in the thermoplastic resin composition.

[0227] In addition, the mass ratio of the tertiary amine contained in the thermoplastic polyurethane (B) can also be measured.

[0228] The sample B was frozen and crushed, and immersed in 10 mL of a 0.01 mol% hydrochloric acid aqueous solution for 3 hours. 0.05 mL of a phenolphthalein solution was added thereto, and neutralization titration was performed with a 0.01 mol% sodium hydroxide aqueous solution. The amount of hydrochloric acid consumed was calculated based on the titration amount, and used as the content of the tertiary amine in the sample B, and the ratio of the content of the tertiary amine in the sample B to the content of the thermoplastic polyurethane (B) was used as the mass ratio of the tertiary amine in the thermoplastic polyurethane (B).

[0229] [Thermoplastic resin composition]

[0230] In the examples and comparative examples described below, the methacrylic resin (A) used as a constituent component of the thermoplastic resin composition is described below.

[0231] <Methacrylic resin (A)>

[0232] As the methacrylic resin (A), methacrylic resins (A-1) to (A-6) produced in the following Production Examples A1 to A6 were used.

[0233] (Production Example A1 (Production of methacrylic resin (A-1)))

[0234] Into a container equipped with a stirrer were placed 2 kg of ion exchange water, 65 g of tricalcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed solution (a).

[0235] Next, 26 kg of ion exchange water was added to a 60 L reactor, the temperature was raised to 80° C., and the mixed solution (a), 21.2 kg of methyl methacrylate, 0.43 kg of methyl acrylate, 27 g of lauroyl peroxide, and 62 g of n-octyl mercaptan were added.

[0236] Next, polymerization was carried out at about 60°C as an initial polymerization temperature for 1 hour, and then the temperature was raised to about 80°C and maintained at about 80°C for suspension polymerization. After the exothermic peak was observed, the temperature was raised to 92°C at a rate of 1°C / min and aged for 60 minutes, thereby substantially completing the polymerization reaction.

[0237] Next, in order to cool to 50°C to dissolve the suspending agent, 20% by mass of sulfuric acid was added, and the polymerization reaction solution was passed through a 1.68 mm mesh sieve to remove agglomerates. The obtained bead polymer was washed, dehydrated and dried to obtain polymer microparticles 1. The polymer microparticles 1 were granulated by a twin-screw extruder to obtain "methacrylic resin (A-1)". The obtained resin had a weight average molecular weight of 102,000, a molecular weight distribution (Mw / Mn) of 1.85, a structural unit of MMA / MA = 98 / 2 mass %, and an unsaturated double bond terminal content of 0.003 mol %.

[0238] (Production Example A2 (Production of methacrylic resin (A-2)))

[0239] Into a container equipped with a stirrer were placed 2 kg of ion exchange water, 65 g of tricalcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed solution (b).

[0240] Next, 26 kg of ion exchange water was added to a 60 L reactor, the temperature was raised to 80° C., and the mixed solution (b), 20.5 kg of methyl methacrylate, 1.32 kg of ethyl acrylate, 33 g of lauroyl peroxide and 22.4 g of n-octyl mercaptan were added.

[0241] Next, suspension polymerization was carried out while maintaining the temperature at about 80° C., and after the exothermic peak was observed, the temperature was raised to 92° C. at a rate of 1° C. / min.

[0242] Then, the mixture was aged for 60 minutes to substantially complete the polymerization reaction.

[0243] Next, in order to cool to 50°C to dissolve the suspending agent, 20% by mass of sulfuric acid was added, and the polymerization reaction solution was passed through a 1.68 mm mesh sieve to remove agglomerates. The obtained bead polymer was washed, dehydrated and dried to obtain polymer microparticles 2. The polymer microparticles 2 were granulated by a twin-screw extruder to obtain "methacrylic resin (A-2)". The obtained resin had a weight average molecular weight of 218,000, a molecular weight distribution (Mw / Mn) of 1.95, a structural unit of MMA / EA=94 / 6% by mass, and an unsaturated double bond terminal content of 0.01 mol%.

[0244] (Production Example A3 (Production of methacrylic resin (A-3)))

[0245] Into a container equipped with a stirrer were placed 2 kg of ion exchange water, 65 g of tricalcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed solution (c).

[0246] Next, 26 kg of ion exchange water was added to a 60 L reactor, the temperature was raised to 80° C., and the mixed solution (c), 21.2 kg of methyl methacrylate, 0.43 kg of methyl acrylate, 27 g of lauroyl peroxide, and 88 g of n-octyl mercaptan were added.

[0247] Next, suspension polymerization was carried out while maintaining the temperature at about 75° C. After the exothermic peak was observed, the temperature was raised to 92° C. at a rate of 1° C. / min and aged for 60 minutes, thereby substantially completing the polymerization reaction.

[0248] Next, in order to cool to 50°C to dissolve the suspending agent, 20% by mass of sulfuric acid was added, and the polymerization reaction solution was passed through a 1.68 mm mesh sieve to remove agglomerates. The obtained bead polymer was washed, dehydrated and dried to obtain polymer microparticles 3. The polymer microparticles 3 were granulated by a twin-screw extruder to obtain "methacrylic resin (A-3)". The obtained resin had a weight average molecular weight of 72,000, a molecular weight distribution (Mw / Mn) of 1.83, a structural unit of MMA / MA=98 / 2 mass%, and an unsaturated double bond terminal content of 0.007 mol%.

[0249] (Production Example A4 (Production of methacrylic resin (A-4)))

[0250] Into a pressure-resistant polymerization reactor equipped with a stirrer, 950 g of methyl methacrylate, 9.6 g of methyl acrylate, 0.2 g of Perhexa 22 as a polymerization initiator, 2.8 g of n-octyl mercaptan, and 240 g of m-xylene were added. The atmosphere in the reaction vessel was replaced with nitrogen, the temperature was raised to 185°C, and the polymerization reaction was carried out for 90 minutes. The contents were taken out, the reactor was washed, and the above reaction was repeated 5 times. The taken out contents were freeze-crushed and then heated to 230°C. Granulation was performed by a degassing extruder to obtain "methacrylic resin (A-4)". The obtained resin had a weight average molecular weight of 76,000, a molecular weight distribution (Mw / Mn) of 1.97, a structural unit of MMA / MA = 99 / 1% by mass, and an unsaturated double bond terminal content of 0.014 mol%.

[0251] (Production Example A5 (Production of methacrylic resin (A-5)))

[0252] Into a container equipped with a stirrer were placed 2 kg of ion exchange water, 65 g of tricalcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed solution (c).

[0253] Next, 26 kg of ion exchange water was added to a 60 L reactor, the temperature was raised to 80° C., and the mixed liquid (c), 21.6 kg of methyl methacrylate, 27 g of lauroyl peroxide, and 62 g of n-octyl mercaptan were added.

[0254] Next, suspension polymerization was carried out while maintaining the temperature at about 75° C. After the exothermic peak was observed, the temperature was raised to 92° C. at a rate of 1° C. / min and aged for 60 minutes, thereby substantially completing the polymerization reaction.

[0255] Next, in order to cool to 50°C to dissolve the suspending agent, 20% by mass of sulfuric acid was added, and the polymerization reaction solution was passed through a 1.68 mm mesh sieve to remove agglomerates. The obtained bead polymer was washed, dehydrated and dried to obtain polymer microparticles 4. The polymer microparticles 4 were granulated by a twin-screw extruder to obtain "methacrylic resin (A-5)". The obtained resin had a weight average molecular weight of 103,000, a molecular weight distribution (Mw / Mn) of 1.83, a structural unit of MMA = 100% by mass, and an unsaturated double bond terminal content of 0.007 mol%.

[0256] (Production Example A6 (Production of methacrylic resin (A-6)))

[0257] Using a container equipped with a stirrer, 95 parts by mass of methyl methacrylate, 5 parts by mass of maleic anhydride, 0.05 parts by mass of lauroyl peroxide, and 0.25 parts by mass of n-octyl mercaptan were added and dissolved to prepare a monomer mixed liquid.

[0258] On the other hand, two glass plates of 250×300 mm in size and 6 mm in thickness were used, and a flexible vinyl chloride gasket was attached near the periphery thereof to prepare a cell in which the distance between the two glass plates was 3.5 mm.

[0259] The monomer mixture liquid was devolatilized for 2 minutes while being stirred under a reduced pressure of 50 torr.

[0260] Next, the decompression is released, the pressure is restored to normal pressure, and the liquid is immediately poured into the glass cell to fill it.

[0261] Next, the mixture was kept in a warm water bath adjusted to 60 to 65°C for 22 hours and then in a hot air circulation oven adjusted to 110°C for 3 hours. The mixture was then left to cool in the room and the glass plate was removed to obtain a sheet-like resin.

[0262] The flake resin obtained as described above was pulverized using a coarse pulverizer Orient Mill VM-42D manufactured by Shinshin Enterprise Co., Ltd. equipped with a 10 mm mesh, and then the pulverized product was passed through a 500 μm mesh sieve to remove fine powder, thereby obtaining a pulverized composition. The crushed composition was granulated by a twin-screw extruder to obtain "methacrylic resin (A-6)". The obtained resin had a weight average molecular weight of 108,000, a molecular weight distribution (Mw / Mn) of 1.92, a structural unit of MMA / MAH = 95.2 / 4.8% by mass, and an unsaturated double bond terminal content of 0.004 mol%.

[0263] [Examples 1 to 4, 6 to 12] [Comparative Examples 1 to 5]

[0264] The methacrylic resin (A), thermoplastic polyurethane (B) and other additives were weighed in the proportions shown in Table 2 and mixed in a tumbler. The mixed raw materials are put into a twin-screw extruder, melt-kneaded (compounded) to generate strands, which are cooled in a water bath and cut with a granulator to obtain pellets. It should be noted that when compounding, a vacuum line is connected to the exhaust section of the extruder to remove volatile components such as water or monomer components under the condition of -0.06MPa. In this way, a thermoplastic resin composition is obtained. It should be noted that the mixing temperature of the thermoplastic resin composition is 230 to 260°C. It should be noted that the numerical values ​​in Table 2 represent the number of parts (mass parts) when the total mass of the methacrylic resin (A) and the thermoplastic polyurethane (B) is 100 parts by mass.

[0265] The mass ratio of the methacrylic resin (A) and the mass ratio of the thermoplastic polyurethane (B) in the thermoplastic resin compositions obtained in Examples 1 to 4, 6 to 9, 11, 12, and Comparative Examples 1 to 5 were analyzed, and the results showed that they were the same mass ratios as those described in Table 2. The mass ratio of the methacrylic resin (A) in the thermoplastic resin composition obtained in Example 10 was 88% by mass, and the mass ratio of the thermoplastic polyurethane (B) was 12% by mass. The mass ratio of the tertiary amine in the thermoplastic resin compositions obtained in Examples 1 to 4, 6 to 12, and Comparative Examples 1 to 5 was 0% by mass, and the mass ratio of the tertiary amine in the thermoplastic polyurethane (B) was 0% by mass.

[0266] [Examples 5 and 13]

[0267] In addition to being used in the manufacture of particles A thermoplastic resin composition was obtained by the same method as in Examples 1 to 4, 6 to 12 and Comparative Examples 1 to 5 except for a single-screw extruder. It should be noted that the kneading temperature of the thermoplastic resin composition was 230°C. The mass ratio of the methacrylic resin (A) and the mass ratio of the thermoplastic polyurethane (B) in the thermoplastic resin compositions obtained in Examples 5 and 13 were analyzed, and the results were the same mass ratios as those described in Table 2. The mass ratio of the tertiary amine in the thermoplastic resin compositions obtained in Examples 5 and 13 was 0% by mass, and the mass ratio of the tertiary amine in the thermoplastic polyurethane (B) was 0% by mass.

[0268] Table 2

[0269]

[0270] <Flat plate sample>

[0271] (Injection Molding)

[0272] The obtained thermoplastic resin composition pellets were put into an injection molding machine and molded into a 100 mm square flat plate with a thickness of 2 mm, which was used as a flat plate sample for evaluation. It should be noted that for the mold, a mold was used in which the mold surface (inside the mold cavity) was ground with a grinding particle size of 8000.

[0273] In addition, the molding conditions of the flat plate sample for evaluation were set as follows.

[0274] Molding temperature (cylinder temperature): 220℃~250℃;

[0275] Mould temperature: 65℃.

[0276] In addition, for the mold temperature during injection molding, in order to improve the transferability of the mold surface ground with a grinding particle size of 8000, it is important to keep it at a higher temperature. When the mold temperature is too high, the cooling time is too long, which is not practical. The temperature range of the mold used to improve its quality is above 40°C and below 100°C, more preferably above 50°C and below 90°C, and further preferably above 60°C and below 85°C. This time, 65°C is selected.

[0277] <ISO dumbbell test piece>

[0278] (Injection Molding)

[0279] The obtained pellets of the thermoplastic resin composition were put into an injection molding machine and molded into ISO No. 1 dumbbell-shaped test pieces as test specimens for evaluation. The molding conditions were in accordance with ISO K6717-2.

[0280] As shown in Table 3, in Examples 1 to 3, 6, 7, 10, 11, and 13, thermoplastic resin compositions having excellent transparency, damage resistance, and toughness and exhibiting good yellowing resistance or processing stability during hot processing can be produced. In Comparative Example 1, injection moldability, processing stability, toughness, and damage resistance are good, but since a thermoplastic polyurethane (B) having a monomer structure derived from polyether as a monomer structure is used, the total light transmittance is low, the haze is high, and the transparency is poor. In addition, the yellowing resistance during hot processing is poor. In Comparative Example 2, injection moldability, processing stability, toughness, and damage resistance are good, but since a thermoplastic polyurethane (B) having a monomer structure derived from an aliphatic isocyanate that is not an alicyclic monomer structure is used, the total light transmittance is poor, the haze is high, and the transparency is poor. In addition, the yellowing resistance during hot processing is at a practically sufficient level but slightly inferior to that of Examples 1 to 3, 6, 7, 10, 11, and 13. In Comparative Example 3, the injection moldability, yellowing resistance during hot working, processing stability and transparency are excellent, but the scratch resistance and toughness are not good. In Comparative Example 4, since the methacrylic resin (A) does not contain other vinyl monomer units other than maleic acid and maleic anhydride that can be copolymerized with the methacrylate monomer, maleic acid and / or maleic anhydride monomer units as the structural units of the methacrylic resin (A), the transparency, scratch resistance and toughness are good, but the yellowing resistance or processing stability during hot working is not good, which is a practically sufficient level compared with Examples 1 to 3, 6, 7, 10, 11, and 13, but the injection moldability is also slightly inferior. In Comparative Example 5, since the methacrylic resin (A) contains a large amount of maleic anhydride monomer units, the transparency, scratch resistance and toughness are good, but the yellowing resistance during hot working and processing stability are not good, and the injection moldability is also a practically sufficient level compared with Examples 1 to 3, 6, 7, 10, 11, and 13, but it is slightly inferior. In Example 4, although the level is sufficient for practical use, the yellowing resistance during hot working is slightly inferior when compared with Examples 1 to 3, 6, 7, 10, 11, and 13. In Example 5, although the level is sufficient for practical use, the transparency and yellowing resistance are slightly inferior when compared with Examples 1 to 3, 6, 7, 9 to 11, and 13. In Example 8, although the level is sufficient for practical use, the yellowing during injection molding is large and there is a tendency for silver streaks to be easily generated when compared with Examples 1 to 3, 6, 7, 10, 11, and 13. Not only is the injection moldability slightly inferior, but the yellowing resistance and processing stability for hot working are also slightly inferior. In addition, the transparency is also sufficient for practical use, but it is slightly inferior compared with Examples 1 to 3, 6, 7, 10, 11, and 13. In Example 9, although the level is sufficient for practical use, the yellowing resistance during hot working is slightly inferior when compared with Examples 1 to 3, 6, 7, 10, 11, and 13.In Example 12, although the level was sufficient for practical use, when compared with Examples 1 to 3, 6, 7, 10, 11, and 13, the injection moldability, yellowing resistance during hot working, and processing stability were slightly inferior.

[0281] Table 3

[0282]

[0283] Industrial Applicability

[0284] According to the thermoplastic resin composition of the present invention, a molded product having good transparency and excellent toughness and scratch resistance can be obtained, and therefore, the composition has industrial applicability as, for example, roofing materials for buildings, automobiles, trains or buses, films for plastic greenhouses, liquid crystal protective films, indoor and outdoor lighting or signs, protective materials for instruments, vehicle interior and exterior components, vehicle lamp components, ship lamp components, battery protective covers, and the like.

Claims

1. A thermoplastic resin composition, wherein: The thermoplastic resin composition contains: 50 to 99% by mass of a methacrylic resin A and 1 to 50% by mass of a thermoplastic polyurethane B. The methacrylic resin A is composed of 80.0 to 99.9% by mass of methacrylic acid ester monomer units, 0.1 to 20.0% by mass of vinyl monomer units composed of vinyl monomers copolymerizable with methacrylic acid ester monomers other than maleic acid and maleic anhydride, and 0 to 4.0% by mass of maleic acid and / or maleic anhydride monomer units; Thermoplastic polyurethane B has a structural unit derived from polyester polyol and a structural unit derived from isocyanate having an alicyclic ring. The isocyanate having an alicyclic ring has one alicyclic ring, and when all structural units derived from isocyanate are taken as 100% by mass, the structural unit derived from isocyanate having one alicyclic ring accounts for 70% by mass or more.

2. The thermoplastic resin composition according to claim 1, wherein The weight average molecular weight of the methacrylic resin A measured by gel permeation chromatography GPC is 50,000 to 250,000.

3. The thermoplastic resin composition according to claim 1 or 2, wherein The molecular weight distribution Mw / Mn of the methacrylic resin A is 1.0 to 6.0, where Mw represents a weight average molecular weight and Mn represents a number average molecular weight.

4. The thermoplastic resin composition according to claim 1 or 2, wherein The amount of unsaturated double bonds at the terminal end of the methacrylic resin A is 0.01 mol% or less.

5. The thermoplastic resin composition according to claim 1 or 2, wherein The vinyl monomer unit composed of a vinyl monomer copolymerizable with a methacrylate monomer other than maleic acid and maleic anhydride is an acrylate monomer unit.

6. The thermoplastic resin composition according to claim 1 or 2, wherein The total content mass ratio of the methacrylic acid ester monomer units and the acrylic acid ester monomer units in 100 mass % of the methacrylic acid-based resin A is 88 mass % or more.

7. The thermoplastic resin composition according to claim 1 or 2, wherein: The methacrylic resin A is composed of 85 to 99.9% by mass of methacrylic acid ester monomer units and 0.1 to 15% by mass of acrylic acid ester monomer units.

8. The thermoplastic resin composition according to claim 1 or 2, wherein The mass ratio of the structural unit derived from isocyanate having one alicyclic ring relative to 100 mass % of the total mass of the structural unit derived from isocyanate contained in the thermoplastic polyurethane B is 90 mass % or more.

9. The thermoplastic resin composition according to claim 1 or 2, wherein The weight average molecular weight of the methacrylic resin A measured by gel permeation chromatography GPC is 85,000 to 190,000.

10. The thermoplastic resin composition according to claim 1 or 2, wherein The amount of unsaturated double bonds at the terminal end of the methacrylic resin A is 0.008 mol% or less.

11. The thermoplastic resin composition according to claim 1 or 2, wherein The total content of the methacrylic resin A and the thermoplastic polyurethane B is 80% by mass or more relative to 100% by mass of the thermoplastic resin composition.

12. The thermoplastic resin composition according to claim 1 or 2, wherein: The impact resistance imparting agent is contained in an amount of 3 to 50% by mass based on 100% by mass of the thermoplastic resin composition.

13. The thermoplastic resin composition according to claim 12, wherein The impact resistance imparting agent is an acrylic rubber multilayer polymer.

14. The thermoplastic resin composition according to claim 1 or 2, wherein: When a flat plate sample with a thickness of 2 mm was prepared using a mold with a grinding grain size of 8000, the total light transmittance was 89% or more.

15. The thermoplastic resin composition according to claim 1 or 2, wherein: When a flat plate sample having a thickness of 2 mm was prepared using a mold having a grinding particle size of 8000, the haze was 10% or less.

16. A method for producing a thermoplastic resin composition, which is the method for producing a thermoplastic resin composition according to any one of claims 1 to 15, characterized in that: The methacrylic resin A and the thermoplastic polyurethane B are mixed at a temperature within a range of 200 to 260°C.

17. A molded body, wherein The molded article comprises the thermoplastic resin composition according to any one of claims 1 to 15.

18. An injection molded body, wherein: The injection-molded article comprises the thermoplastic resin composition according to any one of claims 1 to 15.

19. A method for producing an injection molded body, wherein: The thermoplastic resin composition according to any one of claims 1 to 15 is molded at a cylinder temperature of 200 to 260°C.

Citation Information

Patent Citations

  • Acrylic resin film and injection molded item with it laminated thereto

    JP2003183471A

  • Thermoplasticizable transparent mixtures of thermoplastic polyurethane and poly(meth)acrylate.

    JP2015532345A

  • Transparent TPU (thermoplastic polyurethanes) / PMMA (polymethyl (METH)acrylate) blends with improved low-temperature impact resistance

    WO2007057242A1

  • Transparent TPU (thermoplastic polyurethanes) / PMMA (polymethyl (meth)acrylate) blends with improved low-temperature impact resistance

    CN101291988A

  • Plastic mixtures comprising thermoplastic polyurethane (tpu) and impact-resistant poly(meth)acrylate

    CN101977994A